A REVIEW OF AIR DISTRIBUTION PATTERNS IN SURGERY ROOMS UNDER INFECTION CONTROL FOCUS - Pereira, M. L.; Tribess, A. (Revista de Engenharia Térmica, 2005)
The problem of airborne contamination in surgical infections still raises discussion. The success of the aseptic methods and the use of medicines for the combat of infections are making most surgeons contempt the danger of the aerial particles course. A detailed knowledge of the characteristics of the contamination sources and of the ventilation system performance used at surgery rooms is necessary to guarantee that the ventilation system supplies the pollutant control in ventilation rates that assure the health and the comfort of the occupants. There are many configurations of air distribution systems and a wide range of potential conditions inside a surgery room that are influenced by their performance. In the same way, it is evident the lack of information in the literature regarding which characteristics of the systems of air treatment have stronger influence on the amount of particles in suspension. This paper provides a review of the distribution patterns and air movement at surgery rooms, describing the importance of airborne particles in the infection process, making a comparative analysis of the efficiency of microbiological control of the main airflow systems, identifying and demonstrating the control strategies that can reduce the risks of airborne contamination in surgical infections.